A Study of the Relationship Between Innovation and Performance Among NPOs in Pakistan. Issue 46 (2nd January 2020) - Anwar, Muhammad; Zaman Khan, Sher; Ali Shah, Syed Zulfiqar
Abstract: Innovation has become a core driver for the success and survival of organizations regardless of their size and nature. A plethora of literature has discussed the importance of innovation in profit-based organizations, while nonprofit organizations (NPOs) have generally been ignored in research. This study examines the influence of the sub-dimensions of innovation on the performance of NPOs. Data were collected through structured questionnaires using a sample size of 309 NPOs operating in the emerging market Pakistan. The hypotheses were tested through structural equation modeling (SEM) in AMOS.21. The results indicate that process innovation and organization innovation have significant positive influence on the performance of NPOs, while product innovation and marketing innovation have insignificant influence on the performance of NPOs. NPOs are advised to give enough attention to process and organization innovation in order to boost their performance. Future researchers are encouraged to test the model in other environmental settings. Implications for practice were discussed.